Equivalence of plasma p‐tau217 with cerebrospinal fluid in the diagnosis of Alzheimer's disease - Therriault, Joseph; Servaes, Stijn; Tissot, Cécile; Rahmouni, Nesrine; Ashton, Nicholas J.; Benedet, Andréa Lessa; Karikari, Thomas K.; Macedo, Arthur C.; Lussier, Firoza Z.; Stevenson, Jenna; Wang, Yi‐Ting; Fernandez‐Arias, Jaime; et al. (Alzheimer's & dementia, 2023)
Plasma biomarkers are promising tools for Alzheimer's disease (AD) diagnosis, but comparisons with more established biomarkers are needed. We assessed the diagnostic performance of p-tau , p-tau , and p-tau in plasma and CSF in 174 individuals evaluated by dementia specialists and assessed with amyloid-PET and tau-PET. Receiver operating characteristic (ROC) analyses assessed the performance of plasma and CSF biomarkers to identify amyloid-PET and tau-PET positivity. Plasma p-tau biomarkers had lower dynamic ranges and effect sizes compared to CSF p-tau. Plasma p-tau (AUC = 76%) and p-tau (AUC = 82%) assessments performed inferior to CSF p-tau (AUC = 87%) and p-tau (AUC = 95%) for amyloid-PET positivity. However, plasma p-tau (AUC = 91%) had diagnostic performance indistinguishable from CSF (AUC = 94%) for amyloid-PET positivity. Plasma and CSF p-tau had equivalent diagnostic performance for biomarker-defined AD. Our results suggest that plasma p-tau may help reduce the need for invasive lumbar punctures without compromising accuracy in the identification of AD. p-tau in plasma performed equivalent to p-tau in CSF for the diagnosis of AD, suggesting the increased accessibility of plasma p-tau is not offset by lower accuracy. p-tau biomarkers in plasma had lower mean fold-changes between amyloid-PET negative and positive groups than p-tau biomarkers in CSF. CSF p-tau biomarkers had greater effect sizes than plasma p-tau biomarkers when differentiating between amyloid-PET positive and negative groups. Plasma p-tau and plasma p-tau performed worse than p-tau and p-tau in CSF for AD diagnosis.